THE ROLE OF HISTORICAL INFORMATION IN CONDUCTING PEDAGOGICAL ACTIVITIES WITH ADOLESCENTS WITH DEVIANT BEHAVIOR - Suleymanova Nodira Inomovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The hatti movement of underage youth is discussed in the article on how the culture of teacher communication plays an important role in working with characteristic adolescents with deviations from social procedures adopted in society, non-observance and violation of them, and strengthening ties between the teacher and the student.